Semiotsko-semantična narava glasbe - Pompe, Gregor (Muzikološki zbornik, 2007)
The purpose of the article is to solve the methodological-epistemological problem of the key position of semiotics and semantics in music. This is solved with the aid of the discovery of the dual nature of musical referentiality (internal and external references) and of the cultural, semiotic-semantic conditionality of the musical narrative.
Keywords: glasba; music; referencialnost; semantics; semantika; semiotics; semiotika